Considering the Effects of Local Impact Disturbance on Deep Sandstone: Exploring Strength Weakening Mechanism - Zhao, Jihe; Jin, Jiaxu; Li, Yanfeng; Wu, Pengfei; Wang, Haibo; Shi, Yingshuang (Archives of Mining Sciences, 2025)
The stability of rock mass is an important safety issue in the process of deep mining, and the dynamic disturbance caused by excavation and blasting is an important factor affecting the stability of rock mass. To deeply understand the mechanical characteristics and damage mechanisms of deep sandstone after local impact disturbance by high prestresses, a self-developed rock disturbance system was used to carry out disturbance followed by a uniaxial compression test (UCT) on the rock samples. The whole process of UCT was monitored utilising acoustic emission (AE) technology, and the particle size and fractal dimension of debris after sandstone failure were analysed to explore its strength-weakening mechanism. The experimental study elucidated the influence mechanism of the coupled action of disturbance frequency f and impact area s on the strength weakening effect of sandstone, i.e., high prestressing force is the prerequisite and dominant factor of rock strength weakening, while the perturbation f and the s accelerate the induced rock damage. The fractal dimension D can be used to quantitatively evaluate the fragmentation characteristics of sandstone disturbed by local impact (between 1.68 and 2.14), and it shows a good linear increasing trend with the increase of local impact disturbance.
Keywords: Deep sandstone; local impact disturbance; uniaxial compression; acoustic emission; fractal dimension